2003
DOI: 10.1038/sj.bjc.6601051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endogenous granzyme B in a subset of human primary breast carcinomas

Abstract: Granzyme B (GrB) is the prototypic member of a serine protease family primarily used by cytotoxic lymphocytes to kill target cells. We report here that, by immunohistochemical staining of paraffin-embedded tumour sections, GrB protein was unexpectedly detected in malignant cells of a subset of breast cancers and their adjacent reactive endothelial and mesenchymal cells in which endogenous retinoblastoma protein (pRB) is overexpressed. The identity of the endogenous GrB was further confirmed experimentally in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…For many years, granzyme B had been thought to be expressed in a limited panel of cells; however, it has recently been found in chondrocytes, 10 neutrophils, 11 and some malignant cells. 12,13 Using immunohistochemical, in Abstract Granzyme B is a unique serine protease, which plays a crucial role for target cell death. Several mechanisms of delivery of granzyme B to target cells have been recently identified.…”
Section: Granzyme B and Its Inhibitor Proteinase Inhibitormentioning
confidence: 99%
“…For many years, granzyme B had been thought to be expressed in a limited panel of cells; however, it has recently been found in chondrocytes, 10 neutrophils, 11 and some malignant cells. 12,13 Using immunohistochemical, in Abstract Granzyme B is a unique serine protease, which plays a crucial role for target cell death. Several mechanisms of delivery of granzyme B to target cells have been recently identified.…”
Section: Granzyme B and Its Inhibitor Proteinase Inhibitormentioning
confidence: 99%
“…Five microgram of total RNAs isolated from cells were treated with RNase free DNase (BD-Pharmingen), and then used to generate first-strand cDNAs using RevertAid TM first strand cDNA synthesis kit with 500 ng oligo (dT) [12][13][14][15][16][17][18] primers. PCR primers were designed with ABI PRISM Primer Express 2.0 (Applied Biosystems) and made by GenoTech Corp. (Korea).…”
Section: Rt-pcrmentioning
confidence: 99%
“…Several studies have suggested that granzyme B is produced by cells other than CTLs and NKs. Granzyme B is produced, in the absence of perforin, by the cells of the reproductive system [15], the granulose cells of human ovaries [16], primary human breast carcinomas [17], and the chondrocytes of articular cartilage [18]. The expression of granzyme B has also been detected in human dendritic cells, where it is up-regulated upon cell activation, and in migrating immature thymocytes [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, GrB has been detected in cancer cells of primary human breast carcinomas (88,89), lung carcinomas (88), urothelial carcinomas (90) and in nasal-type NK/T-cell lymphoma (91). Recently, GrB expression was revealed by immunohistochemistry in oral squamous cell carcinoma and it seems to be localized also in cancer cells (92).…”
Section: Granzyme B Gene Organization and Regulation Of Expressionmentioning
confidence: 99%